Exploring the therapeutic affordances of self-harm online support communities: an online survey of members - Coulson, Neil S.; Bullock, Emma; Rodham, Karen (JMIR Publications, 2017)
Background: A growing number of online communities have been established to support those who self-harm. However, little is known about the therapeutic affordances arising from engagement with these communities and resulting outcomes.